2010
DOI: 10.1093/ntr/ntq211
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Home Smoking Bans to the Physical and Mental Health of Smokers

Abstract: Findings are considered with respect to the internal and external constraints that shape smoker's behavior, particularly the influence of social norms around environmental tobacco smoke exposure and good citizenship and the role of family relationships. The implications of study findings are considered with respect to public health policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A recent study in Canada has shown that home smoking ban is associated with improved smokers' mental health but did not affect their physical health 21 . However, the situation is far more complex as various internal and external factors shape smoker's behaviour, particularly the influence of social norms around environmental tobacco smoke exposure, good citizenship and the role of family relationships.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study in Canada has shown that home smoking ban is associated with improved smokers' mental health but did not affect their physical health 21 . However, the situation is far more complex as various internal and external factors shape smoker's behaviour, particularly the influence of social norms around environmental tobacco smoke exposure, good citizenship and the role of family relationships.…”
Section: Discussionmentioning
confidence: 97%
“…In USA, it was observed that young adults with a home ban during late adolescence were less likely to be smokers and less likely to progress to higher use later (Mathur et al 2014). In Canada, home smoking ban was found to be positively associated with smokers' mental health among Canadian adults, being consistent for daily smokers and occasional smokers (Asbridge et al 2011). Similarly, in Scotland, It was observed to benefit adult cardiovascular and mental health as well (Shiue 2014a).…”
Section: Previous Researchmentioning
confidence: 98%
“…Smoke-free policies at home and in the car may result in improving the psychological adjustment of smokers by creating smoke-free environments that will ultimately help smokers in their efforts to stop smoking (Farkas, Gilpin, Distefan, & Pierce, 1999; Gilpin, White, Farkas, & Pierce, 1999; Mills, et al ., 2009; Asbridge & Cartwright, 2011). Smoking bans may facilitate a feeling of confidence that one can take control of a potentially harmful part of one’s life.…”
mentioning
confidence: 99%